Influence of UV dose on the UV/H2O2 process for the degradation of carbamazepine in wastewater. Issue 23 (15th October 2019) - Somathilake, Purnima; Dominic, John Albino; Achari, Gopal; Langford, Cooper H.; Tay, Joo-Hwa
ABSTRACT: This study evaluates the influence of UV dose on degradation of carbamazepine (CBZ) in wastewater under UV-C (λ = 254 nm) photolysis with and without H2 O2 . The rate of degradation of CBZ exhibited a direct dependence on the intensity of incident UV irradiation as the rate of degradation was observed to increase linearly ( R 2 = 0.98) with UV intensity between 1.67 and 8.95 × 10 17 photons/s. More than 95% of the CBZ that spiked in wastewater rapidly degraded within 4 min with a first-order rate constant of 1.2 min −1 for an optimum H2 O2 dose of 100 mg/L. Bench-scale continuous flow reactor experiments also showed that CBZ degraded with first-order kinetics at a rate constant of 1.02 min −1 . The kinetic parameters obtained for a continuous bench-scale reactor were in good agreement with the relationships developed through batch experiments with only a marginal deviation of ± 6.5%. The relationship between UV intensity and CBZ degradation rate obtained in this study was extrapolated to the UV disinfection unit of a wastewater treatment plant to predict possible degradation of CBZ during UV disinfection. The addition of 100 mg/L of H2 O2 to the secondary-treated effluent entering the UV disinfection unit is predicted to achieve over 60% degradation of CBZ. Abbreviations: CBZ carbamazepine; AOPs advanced oxidation processes; UV ultraviolet radiation; UV-C ultraviolet C ( λ = 254 nm) radiation; NZVI non-zerovalent iron; WWTP wastewater treatment plant; HPLC high-performance liquid chromatography GRAPHICAL ABSTRACT: